2021
DOI: 10.1017/s1463423621000475
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms among clients attending monk healers and primary care clinics in Thailand: a comparative follow-up study

Abstract: Background: The aim of this study was to conduct a comparative follow-up assessment of clients with depressive symptoms attending monk healers or primary care clinics in Thailand. Methods: Consecutively attending clients of three monk healing and three primary care centres who screened positive (a score of 9 or more) on the Primary Health Questionnaire (PHQ)-9 at the study site were followed up at 3 months after baseline assessment. Results: In 3 monk healer sites, 448 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…Previous studies have shown increased use of traditional and complementary practitioners for depressive symptoms, 42 possibly due to the better perceived management of depressive symptoms by complementary practitioners than conventional practitioners. 43 The findings of healthcare utilisation are consistent with previous research in Korea and China in terms of outpatient clinic visits and hospital admission. 4 19 20 In univariable analyses, we further found a positive association between depressive symptoms and and medical check-up, while the Korea study 19 found a negative association with medical check-up.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have shown increased use of traditional and complementary practitioners for depressive symptoms, 42 possibly due to the better perceived management of depressive symptoms by complementary practitioners than conventional practitioners. 43 The findings of healthcare utilisation are consistent with previous research in Korea and China in terms of outpatient clinic visits and hospital admission. 4 19 20 In univariable analyses, we further found a positive association between depressive symptoms and and medical check-up, while the Korea study 19 found a negative association with medical check-up.…”
Section: Discussionsupporting
confidence: 89%
“…Our study found that depressive symptoms was associated with increased odds of hospital inpatient, hospital outpatient, health centre outpatient and traditional medicine practitioner utilisation. Previous studies have shown increased use of traditional and complementary practitioners for depressive symptoms,42 possibly due to the better perceived management of depressive symptoms by complementary practitioners than conventional practitioners 43. The findings of healthcare utilisation are consistent with previous research in Korea and China in terms of outpatient clinic visits and hospital admission 4 19 20.…”
Section: Discussionsupporting
confidence: 88%
“…These findings align with prior research, which has highlighted the crucial involvement of monks as invaluable resources in delivering essential mental health support, a role that has earned substantial trust from the wider societal realm (Chaisitida 2005;Pengpid and Peltzer 2020). Individuals who sought therapy from monk healers experienced a reduction in depressive scores (Pengpid and Peltzer 2021). However, individuals tend to seek mental health support that is in line with their unique personality traits (Çekici 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The internal consistency of the measure in this study is high, with Cronbach’s α = 0.91. The scale has been used in our countries of interest [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%